2019
DOI: 10.1115/1.4042057
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Vane Endwall Film Cooling Comparison From Five Film-Hole Design Patterns and Three Upstream Injection Angles

Abstract: The effects of upstream injection angle on film cooling effectiveness of a turbine vane end wall with various endwall film-hole designs were examined by applying pressure-sensitive paint (PSP) measurement technique. As the leakage flow from the slot between the combustor and the turbine vane is not considered an active source to protect the vane endwall in certain engine designs, discrete cylindrical holes are implemented near the slot to create an additional controllable upstream film to cool the vane end wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The confidence level is 95% for the EXP result and the uncertainties of η=0.1,0.3,0.5,0.7 are 12%, 5.4%, 3.1%, 2.2%, respectively. 21 The comparison of the η distribution on the endwall among EXP and CFD results is presented in Figure 11. The η downstream of each row film hole has been predicted more accurately by SST kω turbulence model than by the other three models.…”
Section: Computational Methods and Verificationmentioning
confidence: 99%
“…The confidence level is 95% for the EXP result and the uncertainties of η=0.1,0.3,0.5,0.7 are 12%, 5.4%, 3.1%, 2.2%, respectively. 21 The comparison of the η distribution on the endwall among EXP and CFD results is presented in Figure 11. The η downstream of each row film hole has been predicted more accurately by SST kω turbulence model than by the other three models.…”
Section: Computational Methods and Verificationmentioning
confidence: 99%
“…Figure 1 shows the experimental vane cascade model from (Shiau et al, 2019) of the Turbine Laboratory of Texas A&M University. Table 1 lists the main geometric parameters of the experimental vane cascade and film holes.…”
Section: Numerical Model and Methods Geometric Modelmentioning
confidence: 99%
“…The aerodynamic and cooling performance of the turbine vane endwall was given by (Friedrichs et al, 1997) and they pointed out that the film cooling layout of the endwall needs to consider the complicated secondary flow vortex structure and the intermixing effect of mainflow and film cooling airflow. In (Shiau et al 2019), they used linear cascade experiments to study the heat transfer and cooling performance of the endwall with 3 rows of upstream film holes and 5 film cooling layouts. The results showed that the film cooling layout combined with the development characteristics of the secondary flow vortex system on the endwall had the excellent cooling performance.…”
Section: Introductionmentioning
confidence: 99%
“…Shifting attention to the platform cooling inside of the passage, Shiau and his coauthors addressed several topics by applying PSP. In Shiau et al (2019), a combination between three upstream injection angles and five film-hole design patterns was experimentally tested, under fixed mainstream (Ma2is = 0.5, Tu1 = 19%) and coolant condition (MFR = 1%, DR = 1.5). Although each endwall film-hole pattern was found to have its unique flow/pressure distribution, the general rule is that the thermal coverage provided by the cooling holes located upstream of the throat is heavily dependent on the capability to suppress the secondary flows.…”
Section: Introductionmentioning
confidence: 99%